New Resinogalea species from Araucaria araucana resin in Chile and reclassification of the genus in the Cryptocaliciomycetidae - Felipe Balocchi; Irene Barnes; Michael J. Wingfield; Rodrigo Ahumada; Cobus M. Visagie (IMA Fungus)
Abstract Araucaria araucana is an ancient conifer, native to the mountain ranges in Chile and Argentina. These trees host a large number of organisms, mainly insects, strongly or even exclusively associated with them. The recent emergence of a novel canker disease on A. araucana has emphasised the importance of fungi associated with these iconic trees and has resulted in the discovery of various new species. In this study, we considered the identity of an unknown calicioid fungus consistently found on resin on the branches of A. araucana. Preliminary phylogenetic analyses placed isolates in the recently described sub-class Cryptocaliciomycetidae, closest to Cryptocalicium blascoi. However, the morphology of the ascomata and its occurrence in a unique niche suggested that the closest relative could be Resinogalea humboldtensis (Bruceomycetaceae, incertae sedis), a fungus with similar sporing structures found on resin of Araucaria humboldtensis in New Caledonia. There are no living cultures or sequence data available for either R. humboldtensis or its supposed closest relative, Bruceomyces castoris, precluding sequence-based comparisons. Morphological comparisons of the sporing structures on A. araucana confirmed that the ascomatal morphology of our unknown calicioid fungus and R. humboldtensis are almost identical and resemble each other more so than B. castoris or Cr. blascoi. A phylogenetic analysis based on the small subunit (SSU), internal transcribed spacer (ITS) and large subunit (LSU) rDNA regions resolved our strains into two clades with Cr. blascoi as its closest relative. Further analyses applying the Genealogical Concordance Phylogenetic Species Recognition (GCPSR) based on ITS, mini chromosome maintenance protein complex (MCM7), RNA polymerase II second largest subunit (RPB2) and translation elongation factor 1-alpha (TEF) gene regions, confirmed that strains represent two new species. Based on our morphological observations and phylogenetic analyses, we introduce two new Resinogalea species, R. araucana and R. tapulicola, and reclassify the genus in the subclass Cryptocaliciomycetidae.